Probing the relationship between soft skills and career adaptability among vocational college graduates - Mohd Puad, Mohd Hazwan; Abd Rahim, Fatin Azrin; Omar, Muhd Khaizer; Sufian Kang, Enio Kang Mohd; Pyng, How Shwu (RSIS International, 2024)
In today's era, the demand for a workforce with the right skills required by employers is very high. Students must equip themselves with additional skills beyond academic achievements and must adapt to the skills required in the workplace before they graduate. This study examines the relationship between soft skills and career adaptability among vocational college graduates. The study interprets the crucial factors and skills influencing career adaptability and success in employability among Technical and Vocational Education and Training (TVET) graduates in the future. The researchers used a correlation study design to explain the relationship between soft skills and career adaptability. This quantitative study involves vocational college institutions in Negeri Sembilan, specifically those majoring in the Electronic Technology field and programs. About 120 graduates were chosen as sample respondents in this study. The survey method used a questionnaire to gather feedback from graduates identified in this research. The researchers used IBM SPSS Statistics to analyze the information obtained using descriptive and inferential statistics. The findings show that the level of soft skills among vocational college graduates is moderate to high. Career adaptability also depicted a similar pattern at a high level. There was a strong and significant correlation between soft skills and career adaptability, and teamwork skills are a dominant factor in explaining the career adaptability of graduates from vocational college.